Hubungan Sosial Ekonomi dan Tingkat Pendidikan terhadap Keinginan Pasien untuk Membuat Gigi Tiruan Lengkap di Rumah Sakit Gigi dan Mulut Prof. Soedomo - , LATIFAH EDLIES TRISNAINI; , drg. Endang Wahyuningtyas, M.S., Sp. Pros (K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
People awareness to replace lost teeth with denture is still low because people not yet realize the function of denture.The objectives of this study was to determine the relationship of socioeconomic and levels of education aboutfull denturethe patientâs desire to makea full denture at Rumah Sakit Gigi dan Mulut Prof. Soedomo. The type of research carried out was cross sectional. A questionnaire in this research contains 14 questions with the Likert scale which given out to 30 respondents who wanted to make full denture at Rumah Sakit Gigi dan Mulut Prof. Soedomo. Validity test using Pearson Product Moment and reliability test using Alpha Croanbach was done to data collected from 30 respondents. The data was analyzed by multiple regression. The result showed that there were positive correlation between socioeconomic and levels of education about the full denture towards the patientâs desire to makes a full denture at Rumah Sakit Gigi dan Mulut Prof. Soedomo (R= 0.958, p<0.05). The conclusion of this study is that socioeconomic and levels of education about full denture has a positive relationship towards the patientâs desire to makea full denture at Rumah Sakit Gigi dan Mulut Prof. Soedomo. Keywords : socioeconomic, levels of education, desire, full denture